Globalisation, domestic inflation and global output gaps: Evidence from the euro area - Alessandro Calza (European Central Bank (ECB), 2008)
This paper tests whether the proposition that globalisation has led to greater sensitivity of domestic inflation to the global output gap (the “global output gap hypothesis”) holds for the euro area. The empirical analysis uses quarterly data over the period 1979-2003. Measures of the global output gap using two different weighting schemes (based on PPPs and trade data) are considered. We find little evidence that global capacity constraints have either explanatory or predictive power for domestic consumer price inflation in the euro area. Based on these findings, the prescription that central banks should specifically react to developments in global output gaps does not seem to be justified for the euro area.
Keywords: E3; F4; 330; global output gap; Globalisation; inflation; Kapazitätsauslastung; International; Inflationskonvergenz; EU-Staaten; Welt